New Siberian “spineless” species of Thalassaphorura Bagnall, 1949 (Collembola, Onychiuridae), with a key to world species of the genus - Kaprus, Igor; Paśnik, Grzegorz (Zootaxa, 2017)
Six new species of Thalassaphorura from South Siberia are described and illustrated: T. aspinata sp. nov., T. sayana sp. nov., T. sibirica sp. nov., T. stebaevae sp. nov., T. stepensis sp. nov. and T. weineri sp. nov. Their affinity with related species is discussed and a comparison of all species without anal spines is presented. The key to the world species of Thalassaphorura and their geographic distribution are also provided.